Response to Article “Antipyretic Potential of 80% Methanol Extract and Solvent Fractions of Bersama abyssinica Fresen. (Melianthaceae) Leaves Against Yeast-Induced Pyrexia in Mice” [Response to Letter] - Tegegne BA; Alehegn AA (Dove Medical Press, 2023)
Bantayehu Addis Tegegne,1 Agumas Alemu Alehegn2 1Department of Pharmacy, College of Health Sciences, Debre Markos University, Debre Markos, Ethiopia; 2Department of Pharmacy, Amhara Public Health Institute, Bahir Dar, EthiopiaCorrespondence: Bantayehu Addis Tegegne, Department of Pharmacy, College of Health Sciences, Debre Markos University, Debre Markos, Ethiopia, Tel +251913326285, Email bantayehuaddis.90@gmail.com